phân tích các đa thức sau thành nhân tử
a)x2+7x+12
b)a10+a5+1
phân tích các đa thức thành nhân tử
a) x2 - 5x + 6
b) 3x2 + 9x -30
c) x2 + 7x + 10
a, \(x^2-5x+6=x^2+x-6x+6=x\left(x-1\right)-6\left(x-1\right)=\left(x-1\right)\left(x-6\right)\)
b, \(3x^2+9x-30=3\left(x^2+3x-10\right)=3\left(x^2-2x+5x-10\right)\)
\(=3\left[x\left(x-2\right)+5\left(x-2\right)\right]=3\left(x-2\right)\left(x+5\right)\)
c, \(x^2+7x+10=x^2+2x+5x+10=x\left(x+2\right)+5\left(x+2\right)=\left(x+2\right)\left(x+5\right)\)
a) x2 - 5x + 6 = (x2-2x)-(3x-6)=x(x-2)-3(x-2)=(x-3)(x-2)
b) 3x2 + 9x -30= 3(x2+3x-10) = 3((x2+5x)-(2x+10)) = 3(x(x+5)-2(x+5)) = 3(x-2)(x+5)
c) x2 + 7x + 10 =( x2+5x)+(2x+10)=x(x+5)+2(x+5)=(x+2)(x+5)
a, \(x^2-5x+6=\left(x-2\right)\left(x-3\right)\)
b, \(3x^2+9x-30=3\left(x^2+3x-10\right)\)
\(=\left(x+5\right)\left(x-2\right)\)
c, \(x^2+7x+10=\left(x+2\right)\left(x+5\right)\)
phân tích đa thức thành nhân tử
a) (x+y)2-8(x+y)+12
b) (x2+2x)2-2x2-4x-3
c) (x2+x)2-2(x2+x)-15
a/ \(\left(x+y\right)^2-8\left(x+y\right)+12\)
\(=\left(x+y\right)\left(x+y-8+12\right)\)
\(=\left(x+y\right)\left(x+y+4\right)\)
==========
b/\(\left(x^2+2x\right)^2-2x^2-4x-3\)
\(=\left(x^2+2x\right)^2-\left(2x^2+4x\right)-3\)
\(=\left(x^2+2x\right)^2-2\left(x^2+2x\right)-3\)
\(=\left(x^2+2x\right)\left(x^2+2x-5\right)\)
===========
c/ \(\left(x^2+x\right)^2-2\left(x^2+x\right)-15\)
\(=\left(x^2+x\right)\left(x^2+x-2-15\right)\)
\(=\left(x^2+x\right)\left(x^2+x-17\right)\)
[---]
Phân tích đa thức thành nhân tử
a) 7x – 14
b) 5x3 - 10x2y +5xy2
c) 25 – x2
a) 7x – 14 = 7(x - 2)
b) 5x3 - 10x2y +5xy2 = 5x(x2 - 2xy - y2) = 5x(x - y)2
c) 25 – x2= (x - 5)(x + 5)
a, \(7\left(x-2\right)\)
c, \(\left(5-x\right)\left(5+x\right)\)
\(a,7x-14=7\left(x-2\right)\\ b.5x^3-10x^2y+5xy^2=5x\left(x^2-2xy+y^2\right)=5x\left(x-y\right)^2\\ c,25-x^2=\left(5-x\right)\left(5+x\right)\)
Phân tích đa thức thành nhân tử
a) 7x – 14
b) 5x3 - 10x2y +5xy2
c) 25 – x2
a, 7x - 14 = 7 ( x - 2 )
b, 5x3 - 10x2y + 5xy2
= 5x ( x2 - 2xy + y2 )
= 5x ( x - y )2
c, 25 - x2 = 52 - x2 = ( 5 - x ) ( 5 + x )
Phân tích đa thức thành nhân tử
A= x2+7x+7y-y2
B= 4x3-4x2+x
C= x2+9y2-9-6xy
\(A=x^2-y^2+7x+7y\)
\(=\left(x-y\right)\left(x+y\right)+7\left(x+y\right)\)
\(=\left(x+y\right)\left(x-y+7\right)\)
\(B=4x^3-4x^2+x\)
\(=x\left(4x^2-4x+1\right)\)
\(=x\left(2x-1\right)^2\)
\(C=x^2-6xy+9y^2-9\)
\(=\left(x-3y\right)^2-9\)
\(=\left(x-3y-3\right)\left(x-3y+3\right)\)
A=\(x^2+7x+7y-y^2=\left(x^2-y^2\right)+\left(7x+7y\right)=\left(x-y\right)\left(x+y\right)+7\left(x+y\right)=\left(x+y\right)\left(x-y+7\right)\)
B=\(4x^3-4x^2+x=x\left(4x^2-4x+1\right)=x\left(2x-1\right)^2\)
C=\(x^2+9y^2-9-6xy=\left(x^2-6xy+9y^2\right)-9=\left(x-3y\right)^2-3^2=\left(x-3y-3\right)\left(x-3y+3\right)\)
Phân tích đa thức thành nhân tử
a)A=x2+7x+7y-y2
b)B=x2+2xy+y2-3x-3y
\(a,A=x^2+7x+7y-y^2\\ =x^2-y^2+7x+7y\\ =\left(x-y\right)\left(x+y\right)+7\left(x+y\right)\\ =\left(x+y\right)\left(x-y+7\right)\)
\(b,B=x^2+2xy+y^2-3x-3y\\ =\left(x+y\right)^2-3\left(x+y\right)\\ =\left(x+y\right)\left(x+y-3\right)\)
Phân tích các đa thức sau thành nhân tử
a) 5a - 20b
b) y2 + 2y - x2 + 1
\(a,=5\left(a-4b\right)\\ b,=\left(y+1\right)^2-x^2=\left(y+1-x\right)\left(x+y+1\right)\)
a) 5a - 20b
= 5 ( a - 4b )
b) y^2 + 2y - x^2 + 1
= ( y^2 + 2y + 1 ) - x^2
= ( y + 1 )^2 - x^2
= ( y + 1 + x ) ( y + 1 - x )
Phân tích đa thức thành nhân tử
a, 7x - 14
b, 2x - 2y + x2 - xy
c, 6x + 12
d, x2 - 8x - 9x2 - 15
a, 7x - 14
= 7(x-2)
b, 2x - 2y + \(x^2\)- xy
= (2x-2y) + (\(x^2\)-xy)
= 2(x-y) + x(x-y)
= (x-y)(2+x)
c, 6x + 12
= 6(x+2)
\(a,=7\left(x-2\right)\\ b,=2\left(x-y\right)+x\left(x-y\right)=\left(x+2\right)\left(x-y\right)\\ c,=6\left(x+2\right)\\ d,\text{Sai đề}\)
Phân tích các đa thức sau thành nhân tử
a) 36a4 – y2
b) x2 - 4xy + 4y2
c) 6x2 - 5x −1
\(a,=\left(6a^2-y\right)\left(6a^2+y\right)\\ b,=\left(x-2y\right)^2\\ c=\left(6x^2-6x\right)+\left(x-1\right)=6x\left(x-1\right)+\left(x-1\right)=\left(x-1\right)\left(6x+1\right)\)
Bài 5. Phân tích các đa thức thành nhân tử
a) (x2-4x)2-8(x2-4x)+15 b) (x2+2x)2+9x2+18x+20
c) ( x+1)(x+2)(x+3)(x+4)-24 d) (x-y+5)2-2(x-y+5)+1
Bài 6. Phân tích các đa thức thành nhân tử
a) x2y+x2-y-1 b) (x2+x)2+4(x2+x)-12
c) (6x+5)2(3x+2)(x+1)-6